Symbiotic readiness: Factors that interfere with the industrial symbiosis implementation - Agudo, Fabiana Liar; Bezerra, Bárbara Stolte [UNESP]; Gobbo Júnior, José Alcides [UNESP] (Elsevier, 2023)
In a context of raw material scarcity and environmental concerns, the Industrial Symbiosis (IS) emerges as a strategy that collaborates to increase the resources circularity and sustainability. Despite its relevance, companies still have difficulties to assess whether they have conditions to implement IS. Therefore, the aim of this paper is to identify factors that interfere with the readiness of co-located companies to implement IS. To achieve this objective, theoretical, empirical and statistical research procedures were employed. As a theoretical procedure, a Symbiotic Readiness Assessment Instrument (SRAI), previously developed, was adapted. For the empirical procedure, a survey with 201 co-located companies in industrial parks was applied using the SRAI adapted. For the statistical procedure, a factor analysis was carried out to obtain the main factors that interfere with the IS implementation. As a result, five factors were identified. In view of this, to assess symbiotic readiness, companies must analyze: the availability of water and energy resources; the possibility of exchanging material resources such as waste and by-products; the accessibility of data, such as production information from others companies; the possibility of sharing information and bonds of trust between co-located industries; and access conditions, infrastructure and partnership for the symbiosis realization.
Keywords: Assessment instrument; Factor analysis; Measurement; Sustainability; Symbiotic readiness